2013
DOI: 10.1002/jctb.4222
|View full text |Cite
|
Sign up to set email alerts
|

Efficient degradation of fulvic acids in water by catalytic ozonation with CeO2/AC

Abstract: BACKGROUND: Fulvic acids (FA), the main organic compounds in landfill leachate, are toxic and bio-resistant organic compounds. Ozonation is effective in removing non-biodegradable components and the addition of catalysts can improve the removal rates. The objective of this study is to prepare and improve CeO 2 /AC catalyst for catalytic ozonation of FA. RESULTS: The cerium precursor, calcination atmosphere and calcination temperature changed the percentage of Ce 3+ on the surface, thus affecting the catalytic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 35 publications
(48 reference statements)
1
17
0
Order By: Relevance
“…The presence of the Ce 3+ /Ce 4+ redox couple on the surface of the catalysts was evidenced by XPS analysis. The complete characterization of this material is reported elsewhere (Qin et al 2014). All other chemicals required in the experiments were analytical grade reagents.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of the Ce 3+ /Ce 4+ redox couple on the surface of the catalysts was evidenced by XPS analysis. The complete characterization of this material is reported elsewhere (Qin et al 2014). All other chemicals required in the experiments were analytical grade reagents.…”
Section: Methodsmentioning
confidence: 99%
“…In our previous work (Qin et al 2014), it was found that CeO 2 /AC could obviously promote commercial fulvic acids (FA) degradation at acidic pH and an increase in the catalytic activity with the increase of the percentage of Ce 3+ on the surface was observed. In addition, experiments carried out in the presence of the radical scavenger tert-butanol supported the involvement of • OH radicals in the oxidation mechanism.…”
Section: Introductionmentioning
confidence: 97%
“…Besides, Hg (II) ions adsorption capacity was improved when amino was introduced into the surface of adsorbent. Actually, nitrogen-containing AC has been developed to remove heavy metals [9] and organic pollutants [10][11][12] from aqueous media. This prompted us to investigate the use of nitrogen-containing carbon materials for the adsorption of Hg (II) ions in water.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a process which can effectively remove humic substances may be considered as an effective treatment method for landfill leachate [1]. Treatment approaches, such as activated carbon adsorption [2], Fenton treatment [3], H2O2 oxidation [4] and ozone-based advanced oxidation processes [5][6][7] have been extensively investigated in the treatment of landfill leachate. Activated carbon adsorption is an effective method for treatment of high concentrated, toxic and biorefractory wastewater.…”
Section: Introductionmentioning
confidence: 99%